THEORITICAL REVIEWS ON AFFECTIVE ASSESSMENT TOWARD THE UNDERSTANDING OF SENIOR HIGH SCHOOL ENGLISH TEACHERS IN PADANG OF WEST SUMATERA - Yulmiati Yulmiati (Universitas Negeri Padang, 2016)
Based on curriculum 2013 demand, assessment in teaching and learning process emphasizes cognitive, affective and psychomotor domain. Cognitive domain is focus on assessing student knowledge. While affective assessment relates to information about students’ behaviour toward the lesson. Then, in psychomotor domain, teacher concerns to assess students’ skill. In other words, smart, good attitude and good skill are important to be acquired by the students. Unfortunately, most of Senior High School teachers in Padang are still confused to implement affective assessment. In fact, assessing affective domain is essential in order to build students’ soft skills. While soft skill will determine students’ success in their future life whether in their job or in their society. However, some schools in the Indonesia, especially in Padang, are not ready to implement curriculum 2013 and they decide to implement curriculum 2006. Thus, this paper explaines theoretically about the concept of affective assessment in teaching learning process. It involves the concept of the level of affective domain, techniques and instruments that can be used on affective assessment. It is hoped that this paper will be considered by English teachers in Indonesia to implement affective assessment because this assessment is ideal in order to know students’ attitudes through the English as Foreign Language